THE IMPACT OF BILINGUALISM ON ENGLISH LANGUAGE ACQUISITION - Raximova Feruzabonu Shodlikbek qizi,; Ne'matova Madina Baxtiyor qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the impact of bilingualism on English language acquisition, focusing on how speaking two or more languages influences cognitive development,  linguistic  awareness,  and  communication  skills.  Bilingualism  is increasingly recognized as an asset in language learning, as it enhances metalinguistic awareness  and  facilitates  the  acquisition  of  additional  languages  like  English. However,  it  can  also  present  challenges  such  as  interference,  code-switching,  and uneven language proficiency. The article discusses both the advantages and difficulties of bilingualism in learning English, emphasizing that bilingual learners possess unique linguistic  flexibility  that  can  accelerate  their  mastery  of  English  when  properly supported by educational strategies.